Non-Voxel-based Interactive Indirect Lighting Using Layered Reflective Shadow Maps - Zhang, Bo; Choi, JinHyung; Su Oh, Kyoung; Il Choi, Hyung (International Journal of Engineering and Technology, 2018)
Background/Objectives: In recent years, global illumination (GI) has become a significant research area in computer graphics. The game industry has a lot of market demand for real-time GI rendering.Methods/Statistical analysis: The key idea of our approach is generating G-buffered layered depth, normal and flux maps (LRSMs) from the light source in the first rendering pass. Subsequently, we sample LRSMs which are stored in GPU memory and combine normal distribution approximation method for deferred shading in the second rendering pass to simulate indirect light.Findings: We present a non-voxel-based interactive indirect illumination algorithm which can approximately calculate the intensity of one-bounce indirect light in traditional graphics pipeline. Without voxelization, we are able to avoid using the complex octree data structure of voxels, which can improve the rendering performance by simplifying the process while obtaining similar results of voxel cone tracing. The test rendering rate in sponza scene reaches average 69.2fps.Improvements/Applications: Our algorithm also supports diffuse and glossy reflection scenes and the objects and light sources are able to dynamically move at a given scene.Â Â Â